Application Diaphragmatic Breathing Exercise on Dypsnea Patients With Pneumonia in Pakuhaji Hospital at Tangerang - Nanda Triocha; Roby Rahmadi Akbar (Journal of Smart Nursing and Health Science, 2023)
Background : Pneumonia is an infection or acute inflammation of the lung tissue caused by various microorganisms, such as bacteria, viruses, parasites, fungi, exposure to chemicals or physical damage to the lungs, which causes patients to complain of shortness of breath. Purpose: to determine the application of Diaphragmatic Breathing Exercise to Reducing the Degree of Dipsnea in patient with pneumonia at. Pakuhaji Regional General Hospital. Method : This study uses the case study method with soul research. perform nursing care for pneumonia patients with ineffective breathing patterns, namely dyspnea in pneumonia patients. The preparation care applies relaxation therapy, namely Diaphragmatic Breathing Exercise in accordance with evidence based practice in these two applications carried out for three days and three valuations. Result : the evaluated data obtained showed that there was a nursing problem with ineffective breathing patterns, so that nursing was implemented to improve the patient's breathing pattern, namely by using diaphragmatic breathing for 3 consecutive days with a duration of 10-15 minutes showing the result that giving diaphragmatic breathing had an effect on reducing degree of dyspnea in pneumonia patients, measuring the degree of dyspnea using the Modify Borg Dypsnea Scale (MBDS) measurement obtained the results of shortness of breath for both patients on the first day of scale 5 (severe dyspnea) to scale 2 (mild dyspnea) after 3 days of intervention. Conclusion: After the intervention was carried out on both patients, it was found that there was a decrease in the degree of dyspnea in pneumonia patients after being given the application of the Diapragmatic Breathing Exercise